Photocatalytic modified asphalt based on g-C3N4 / CeO2 / Bi2O3 / TOM

By introducing g-C3N4/CeO2/Bi2O3/TOM photocatalyst into asphalt materials, the deficiencies of existing asphalt materials in high-temperature rutting resistance, low-temperature cracking resistance and exhaust gas purification are solved, achieving more efficient exhaust gas degradation and material performance improvement. .

CN119330638APending Publication Date: 2025-01-21ARMY ENG UNIV OF PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381310.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing asphalt materials have shortcomings in high-temperature rutting resistance, low-temperature cracking resistance, ultraviolet aging and long-term aging, and it is difficult to effectively purify exhaust pollutants.

Method used

Asphalt modified based on g-C3N4/CeO2/Bi2O3/TOM photocatalyst is used to improve its photocatalytic performance and durability by combining the photocatalyst with the asphalt material. The modified asphalt uses a specific preparation process, including ultrasonic treatment, magnetic stirring and pH adjustment, to ensure that the photocatalyst is evenly dispersed in the asphalt and works efficiently.

Benefits of technology

It achieves efficient degradation of different components in exhaust gas under different light source conditions, improves the high-temperature stability and low-temperature crack resistance of asphalt materials, and the material cost is low and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330638A_ABST
    Figure CN119330638A_ABST
Patent Text Reader

Abstract

The invention discloses photocatalytic modified asphalt based on g-C3N4 / CeO2 / Bi2O3 / TOM. According to the invention, an organic long chain DC5700 is grafted to the surface of a photocatalyst so as to improve the compatibility of the photocatalyst and an asphalt material. Under different light source conditions, the degradation effects on different components in tail gas are different, and compared with a traditional asphalt material, the degradation effect is more efficient. After the photocatalyst is added into asphalt, the permanent deformation of an asphalt material can be reduced, and the high-temperature stability is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified asphalt, in particular to a g-C3N4 / CeO2 / Bi2O3 / TOM-based photocatalytic modified asphalt, belonging to the technical field of asphalt. Background Art

[0002] The g-C3N4 / CeO2 / Bi2O3 / TOM photocatalyst is a new type of material developed through technical means. Photocatalysts are added to cement or asphalt materials to prepare photocatalytic cement or asphalt.

[0003] The photocatalyst g-C3N4 / CeO2 / Bi2O3 / TOM under different doping ratios was selected and added to asphalt to determine whether it has the function of purifying exhaust gas, and compared with the single photocatalytic material to determine the difference in exhaust gas purification efficiency between the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalyst and other photocatalytic materials.

[0004] The high-temperature anti-rutting performance, low-temperature anti-cracking performance, UV aging and long-term aging phenomena of asphalt are studied, and the various properties of asphalt materials are analyzed through tests and data on base asphalt and photocatalytic modified asphalt. The experimental types include temperature scanning (TS) test, multi-stress creep recovery (MSCR) test, linear amplitude scanning (LAS) test, UV aging test (QUV), long-term aging (PAV) test and bending beam rheology test (BBR).

[0005] The dispersion of photocatalyst in asphalt was analyzed by optical microscope to study the appropriate dosage ratio of photocatalyst. The optimal dosage ratio of photocatalyst was determined by combining the exhaust gas degradation efficiency and the impact on various properties of asphalt. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocatalytic modified asphalt based on g-C3N4 / CeO2 / Bi2O3 / TOM.

[0007] In the first aspect, the present invention provides a g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic modified asphalt, the modified asphalt comprising a base asphalt and a grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material accounting for 2 to 8 wt% of the base asphalt mass; wherein the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material is prepared by adding the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material to a mixture of deionized water and anhydrous ethanol. The mixed solution was ultrasonically treated for 30 minutes, and the obtained mixed solution was magnetically stirred at 25°C for 15 minutes, the pH value was adjusted to 12-14, and then a 40% methanol solution of (trimethoxysilylpropyl) octadecyldimethylammonium chloride (DC5700) was added, and stirred at 1500rmp for 3 hours at 50°C, and then stirred at 300rmp for 1 hour. The impurities were removed by washing and filtering for multiple times, and the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material was obtained after drying.

[0008] Preferably, the volume ratio of deionized water to anhydrous ethanol in the mixed solution of deionized water and anhydrous ethanol is 4:1.

[0009] Preferably, the 40% methanol solution of DC5700 is obtained by dissolving DC5700 in a methanol solution having a concentration of 40 wt %.

[0010] Preferably, the mass ratio of g-C3N4 / CeO2 / Bi2O3 / TOM to DC5700 is 1:2.

[0011] Preferably, the pH value is adjusted to 12-14 using aqueous ammonia.

[0012] Preferably, the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material is prepared by the following steps:

[0013] Step 1: Place g-C3N4, CeO2 and Bi(NO3)3·5H2O in a mixed solution of anhydrous ethanol and deionized water, stir evenly, add tourmaline powder, disperse by ultrasonic for 1 h, and then stir by magnetic stirring for 2 h;

[0014] Step 2: After drying the suspension obtained in step 1, the obtained block solid is ground into powder;

[0015] Step 3: Keep the above powder at 500°C for 4 hours, and then keep it at 450°C for 12 hours, and obtain g-C3N4 / CeO2 / Bi2O3 / TOM heterojunction photocatalytic material after cooling.

[0016] Specifically, g-C3N4 is prepared by the following steps: heating dicyandiamide at 600°C for 4 hours at a heating rate of 15°C / min; and obtaining g-C3N4 after cooling.

[0017] Specifically, the mass ratio of g-C3N4, CeO2 and Bi(NO3)3·5H2O is 3:4:14.55; the mass of tourmaline is 15% of the total mass of g-C3N4, CeO2 and Bi(NO3)3·5H2O.

[0018] Specifically, the volume ratio of anhydrous ethanol to deionized water is 5:3.

[0019] Specifically, the obtained suspension was dried at 80° C. for 12 h to obtain a block solid, which was ground into powder and placed in a ceramic crucible.

[0020] Specifically, the temperature was increased to 500° C. at a heating rate of 15° C. / min, and then kept at 450° C. for 12 h.

[0021] In a second aspect, the present invention provides a method for preparing the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic modified asphalt according to the first aspect, comprising the following steps:

[0022] The base asphalt is heated to 150±5°C, mixed with the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material in a mixer at 300rpm and stirred for 30 minutes, and then sheared and stirred for 90 minutes at 2000rpm using a high-speed shearing machine to obtain the photocatalytic modified asphalt.

[0023] Compared with the prior art, the present invention has the following technical effects:

[0024] (1) Compared with the prior art, the present invention adds g-C3N4 / CeO2 / Bi2O3 / TOM photocatalyst to asphalt, realizing the function of utilizing sunlight energy to catalytically degrade tail gas pollutants, and can be used in the fields of highway construction and municipal road construction of any grade. The present invention requires less photocatalyst to be added, and the optimal dosage is about 4% after experiments. The material cost is low, no toxic substances are released during the reaction, and it is environmentally friendly.

[0025] (2) The degradation effects on different components in exhaust gas are different under different light source conditions. Compared with traditional asphalt materials, the degradation effect is more efficient.

[0026] (3) After the photocatalyst of the present invention is added to asphalt, the permanent deformation of the asphalt material can be reduced and the high-temperature stability is better.

[0027] (4) The photocatalytic material of the present invention is low-priced and easy to operate, and can be used as a new type of pavement asphalt modification material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The degradation efficiency of g-C3N4 / CeO2 / Bi2O3 / TOM composite photocatalyst formed at different mass ratios for four components of exhaust gas; (a) HC; (b) CO; (c) CO2; (d) NO X .

[0029] Figure 2 The complex shear modulus results of modified asphalt with different photocatalyst incorporation ratios are as follows: (a) photocatalyst modification; (b) UV aging; (c) PAV aging.

[0030] Figure 3 This is a typical data chart for the MSCR test.

[0031] Figure 4 This is the stress-strain curve in LAS.

[0032] Figure 5 This is the damage characteristic curve of LAS.

[0033] Figure 6 This is a photocatalytic modified asphalt sample.

[0034] Figure 7 This is the bending rheometer diagram.

[0035] Figure 8 This is the relationship diagram between creep stiffness S and photocatalyst dosage of photocatalytically modified asphalt at different temperatures.

[0036] Fig. 9 This is the relationship diagram between the creep rate m of photocatalytically modified asphalt and the photocatalyst dosage at different temperatures.

[0037] Fig.10 Photo of photocatalytically modified asphalt sample coated on glass plate.

[0038] Fig.11 Figure 2 shows the degradation efficiency of exhaust gas by photocatalytic modified asphalt samples; (a) The degradation efficiency of exhaust gas by each sample under ultraviolet light; (b) The degradation efficiency of exhaust gas by each sample under natural light; (a1) HC; (a2) CO; (a3) ​​CO2; (a4) NO X ;(b1)HC;(b2)CO;(b3)CO2;(b4)NO X .

[0039] Fig.12 This is a picture of the modified asphalt slide sample with different photocatalyst dosages.

[0040] Fig.13 Dispersion degree of different dosages of photocatalyst in asphalt; (a) 0wt%; (b) 2wt%; (c) 4wt%; (d) 6wt% and (e) 8wt% (×100). DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with specific examples, but the scope of protection of the present invention is not limited thereto. In addition, it should be understood that after reading the contents of the present invention, those skilled in the art can make various changes and modifications to the present invention, and the modifications of equivalent forms also fall within the scope limited by the rights of this application.

[0042] The present invention prepares a g-C3N4 / CeO2 / Bi2O3 / TOM heterojunction photocatalytic material based on photocatalytic technology, which can change the structure type of the crystal, effectively inhibit the recombination of photogenerated electron-hole pairs of the material, improve the photocatalytic effect of the photocatalyst, and improve the degradation efficiency of the photocatalyst.

[0043] The g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material prepared by the present invention is a powdered inorganic material with good chemical stability and weak alkalinity, while asphalt belongs to a polymer organic material. If the photocatalytic material is directly added to the asphalt as a modifier, the two materials may be incompatible, which may affect the performance of the photocatalytic modified asphalt. Therefore, the present invention grafts organic long-chain (trimethoxysilylpropyl) octadecyl dimethyl ammonium chloride DC5700 onto the surface of the photocatalyst to improve its compatibility with the asphalt material.

[0044] The present invention conducts dynamic shear tests on original asphalt, residual asphalt samples after aging in a rotating thin film oven test (RTFOT), and a pressure accelerated aging test (PAV), and uses the complex shear modulus G*, the phase angle δ, and the rutting factor G* / sinδ and fatigue factor G*·sinδ calculated from the two as evaluation indicators to evaluate the high-temperature rutting resistance and medium-temperature fatigue resistance of the asphalt binder. The creep stiffness S and creep rate m of the photocatalytic modified asphalt are measured by a bending beam rheology test (BBR) to evaluate the low-temperature crack resistance of the asphalt.

[0045] Example 1

[0046] Preparation of g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic materials

[0047] Step 1. First, weigh 3g g-C3N4, 4g CeO2 and 14.55g Bi(NO3)3·5H2O respectively and disperse them in a mixed solution formed by 50mL of anhydrous ethanol and 30mL of deionized water, stir evenly, then weigh 1.08g of tourmaline powder (5%) and add it, first try to use ultrasonic dispersion for 1h, and then use a magnetic stirrer to stir for 2h.

[0048] Step 2: Dry the suspension obtained in step 1 in an oven at 80° C. for 12 h to obtain a block solid, grind it into powder and place it in a ceramic crucible.

[0049] Step 3: Place the ceramic crucible in a muffle furnace and keep it at 500°C for 4 hours, with a heating rate of 15°C / min. Then keep it at 450°C for 12 hours. After calcination and cooling, the sample obtained is the g-C3N4 / CeO2 / Bi2O3 / TOM composite photocatalytic material, which is dark yellow-black.

[0050] Step 4. According to the above method, 5%, 10%, 15% and 20% of tourmaline are added to the total mass of g-C3N4, CeO2 and Bi(NO3)3·5H2O, respectively, to prepare four g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic materials with different mass ratios.

[0051] The performance of g-C3N4 / CeO2 / Bi2O3 / TOM composite photocatalysts with four mass ratios was tested, and the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalyst with the best mass ratio was obtained, such as Figure 1 shown.

[0052] From the above, it can be obtained that tourmaline accounts for 15% of the mass of the ternary composite material (optimal mass ratio).

[0053] Example 2

[0054] Preparation of Grafted g-C3N4 / CeO2 / Bi2O3 / TOM Photocatalytic Materials

[0055] (1) Weigh 5 g of g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material, add it to a mixed solution of 80 ml of deionized water and 20 ml of anhydrous ethanol, and perform ultrasonic treatment for 30 minutes.

[0056] (2) The obtained mixed solution was magnetically stirred at 25°C for 15 minutes.

[0057] (3) Slowly add concentrated ammonia water to the mixed solution to adjust the pH of the mixed solution to about 12, and then add 40% methanol solution of DC5700, wherein the 40% methanol solution of DC5700 is obtained by dissolving 10 g of DC5700 in 200 ml of 40% methanol solution.

[0058] (4) The mixed solution obtained in step (3) was stirred at 1500 rpm for 3 hours at 50°C, and then stirred at a low speed for 1 hour.

[0059] (5) Repeat filtering the mixed solution obtained in step (4) three times with deionized water and methanol solution to remove excess impurities. Finally, place it in an oven at 80° C. and dry it for 12 hours. The obtained solid material is the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material.

[0060] Example 3

[0061] Preparation of photocatalytic modified asphalt

[0062] The base asphalt was heated to 150±5°C, mixed with the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material samples (accounting for 0wt%, 2wt%, 4wt%, 6wt% and 8wt% of the asphalt mass, respectively) in a mixer at 300rpm and stirred for 30 minutes. Then, a high-speed shearing machine was used to continue shearing and stirring at 2000rpm for 90 minutes. After that, the photocatalytic modified asphalt was obtained.

[0063] Experimental test results

[0064] (1) Performance test of g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic modified asphalt (temperature scanning TS)

[0065] Because asphalt materials are sensitive to temperature changes, the present invention uses a temperature scanning (TS) test in DSR to measure the two main parameters of the complex shear modulus and phase angle of the photocatalytic modified asphalt to analyze the effect of the photocatalyst on the high-temperature performance of asphalt. In actual pavement applications, asphalt materials are subject to aging, so the PAV test is used to simulate the long-term aging process of the asphalt material, and the UV aging box is used to simulate the UV aging process. Then, the temperature scanning test in the DSR dynamic shear rheometer is used to measure the complex shear modulus G* and phase angle δ of the photocatalytic modified asphalt and its long-term UV aging, and the double logarithm of G* and time is taken for data fitting. Among them, G* can be used to characterize the total resistance of the photocatalytic modified asphalt material under repeated shear deformation, including the elastic component and viscous component of the photocatalytic modified asphalt; δ can be used to evaluate the elastic properties of the photocatalytic asphalt material. Under high temperature conditions, if the phase angle of the modified asphalt material is large, it means that the elastic part of the asphalt material accounts for a small proportion under high temperature conditions, and the ability to recover deformation is weak, and the high temperature stability is poor; under low temperature conditions, the smaller the phase angle of the asphalt material, the poorer the deformation ability, which is not conducive to the low temperature crack resistance of the material. The temperature sensitivity of the photocatalytic modified asphalt before and after aging is analyzed through temperature scanning tests, so as to study the effect of photocatalysts on the high temperature performance of asphalt materials.

[0066] Figure 2 The complex shear modulus results of modified asphalt with different photocatalyst incorporation ratios are given. The relationship between the complex shear modulus G* and temperature of photocatalytic modified asphalt after UV aging and PAV aging. Figure 2 It can be clearly seen that with the increase of temperature, G* shows a downward trend. Figure 2 From (a), we can see that with the increase of the amount of photocatalytic material, G* first increases and then decreases. When the mass ratio of the doped photocatalyst is 4wt% of the asphalt mass, the G* value of the modified asphalt is the largest. This shows that the less sensitive it is to temperature, the better its high temperature stability. Figure 4 As can be seen in (b), after UV aging, the G* of samples with different doping ratios decreases first and then increases as the temperature rises. The G* of the sample with a doping ratio of 6wt% is the smallest and is smaller than that of the base asphalt, while the G* of the samples with the other three doping ratios after UV aging are not much different and are all larger than the base asphalt. Figure 4In (c), we can see that the G* of each sample material after PAV aging is not much different. And as the temperature of each sample material increases (for example, from 30℃ to 80℃), the G* gradually decreases, and the maximum difference can be seen to be about 1000 times. This shows that temperature has a great influence on the complex shear modulus of asphalt materials, which also reflects from the side that asphalt will become softer under high temperature conditions and is more likely to deform than under low temperature conditions, so it is more likely to produce rutting in summer.

[0067] (2) Multi-stress creep recovery test (MSCR)

[0068] The Federal Highway Administration of the United States proposed the use of a multi-stress creep recovery test to evaluate the high-temperature anti-rutting performance of asphalt. According to the specification AASHTO TP 70-12, the test is carried out at two stress levels of 0.1kPa and 3.2kPa, where each stress level needs to go through 10 cycles, and each cycle lasts for 10s. One cycle in the test consists of a 1s creep stage plus a 9s unloading recovery stage. The total test time lasts for 200s, and the deformation recovery rate R and irrecoverable creep compliance Jnr are finally used as evaluation indicators. The creep recovery rate R and irrecoverable creep compliance Jnr of each sample can be calculated by the following formula.

[0069]

[0070] Among them, γ p is the strain peak, γ nr is the residual strain, γ0 is the initial strain, and τ is the creep stress.

[0071] The MSCR test is still completed using the DSR test equipment. Figure 3 is the time-accumulated strain result in the MSCR test of photocatalytic modified asphalt. According to formula (1.1), the recovery rate index of photocatalytic modified asphalt can be calculated and recorded as R 0.1 and R 3.2 ; According to formula (1.2), the irreversible creep compliance J can be calculated nr , respectively denoted as J nr0.1 and J nr3.2 . In the present invention, the base asphalt and the modified asphalt with a photocatalyst content of 2wt%, 4wt%, 6wt% and 8wt% are recorded as J1, J2, J3, J4 and J5 respectively; the base asphalt treated with UV aging and the modified asphalt with a photocatalyst content of 2wt%, 4wt%, 6wt% and 8wt% are recorded as U1, U2, U3, U4 and U5 respectively; the base asphalt treated with PAV and the modified asphalt with a photocatalyst content of 2wt%, 4wt%, 6wt% and 8wt% are recorded as P1, P2, P3, P4 and P5 respectively. Then R and J can be obtained. nrThe values ​​are shown in Table 1.

[0072] Table 1 R and J nr The calculated value of

[0073]

[0074]

[0075] The experimental temperature selected by the present invention is 64°C, which is mainly because asphalt pavement is more likely to produce rutting when the temperature is above 60°C. It can be seen from Table 1 that with the increase of the photocatalyst dosage, the deformation recovery capacity R first increases and then decreases, indicating that when the temperature rises, the elastic recovery of the modified asphalt material first increases and then decreases. When the photocatalytic dosage is about 6wt%, the R value is the largest, indicating that the elastic deformation recovery rate of the photocatalytic modified asphalt at this dosage is the highest; and for all asphalt samples, it can be seen that its R0.1 is greater than R3.2, indicating that the shear deformation of the photocatalytic modified asphalt at a high stress level is more difficult to recover than the shear deformation at a low stress level. Jnr shows a phenomenon of first decreasing and then increasing, indicating that under high temperature conditions, with the increase of temperature, the high temperature stability of the modified asphalt gradually increases, and when the photocatalyst dosage is about 4%, the Jnr value is the smallest, indicating that the photocatalytic material at this dosage has the best elasticity and the strongest anti-rutting ability for improving the asphalt binder. Therefore, a certain dosage of photocatalyst has an improving effect on the high temperature anti-rutting property of asphalt.

[0076] (3) Linear Amplitude Sweep Test (LAS)

[0077] The linear amplitude sweep test (LAS) used in the asphalt rheology test can be used to evaluate the fatigue performance of asphalt. The present invention uses the modified asphalt sample after PAV aging to perform the LAS test, and then evaluates the fatigue performance of the photocatalytic modified asphalt. The LAS test operation procedure is simple, the test time is short, and the data processing is also relatively convenient.

[0078] In order to evaluate the fatigue strength of photocatalytically modified asphalt, the medium temperature was selected as 19°C according to the PG grade specification of the asphalt grade used in the test. Therefore, the present invention carried out a linear amplitude scanning test of different doses of photocatalytically modified asphalt at a temperature of 19°C. Figure 4 The stress-strain curves of different amounts of photocatalytic modified asphalt are shown. Figure 4It can be seen that the shear stress first increases rapidly with the increase of shear strain. Except for the 8% dosage, the photocatalytic modified asphalt materials at other dosages reach the maximum value when the shear strain is about 10%. Compared with the base asphalt, the modified asphalt maintains a lower stiffness at low shear strain, and the stiffness decreases more significantly when the dosage is greater than 4%. At high shear strain, all samples slowly approach zero. However, the drop is more obvious for the modified asphalt with a photocatalyst dosage of 8%.

[0079] Figure 5 is the relationship between the damage parameter C and the damage strength S. When the C value decreases to zero, it indicates that the asphalt material has been completely destroyed. The faster the C value decreases in the figure, the faster the damage occurs. Figure 5 It can be seen that when the photocatalyst content is less than 4wt%, the samples have similar destruction points compared to the base asphalt, but slightly larger than the base asphalt. When the photocatalyst content is 8wt%, the C value drops rapidly and reaches zero value at the earliest. This shows that the destruction of the modified asphalt with a photocatalyst content of 8wt% occurs fastest and earliest. In addition, when the photocatalyst content is less than 4wt%, the fatigue performance of the asphalt material will not decrease, and may even be slightly improved.

[0080] (4) Bending beam rheology test (BBR)

[0081] Under low temperature conditions, the hardness of asphalt materials is large but brittle, and the phenomenon of low temperature fracture is prone to occur. When the temperature drops to a certain range, the asphalt material shrinks and tensile stress will appear inside. When this stress value reaches the stress state that it can bear the most, the asphalt material will be damaged. Therefore, in order to evaluate the low temperature stability of photocatalytic modified asphalt, the present invention selects the BBR test proposed in the US Highway Strategic Research Program (SHARP Program). The creep stiffness (S) and creep rate (m) of the photocatalytic modified asphalt under low temperature conditions are obtained in the test to evaluate the low temperature crack resistance of the material. Among them, the creep stiffness S value represents the ability of the asphalt material to resist permanent deformation, which is a characterization parameter of its resistance to external loads. Under low temperature conditions, if the measured S value is larger, it means that the brittleness of the sample is larger, so the use of this asphalt will cause the low temperature crack resistance of the asphalt pavement to be poor; the creep rate m value represents the rate of change of the stiffness of the asphalt material under load. If the measured m value is larger, it means that the stress relaxation ability of the sample is larger, indicating that this asphalt material will have better crack resistance at low temperatures.

[0082] Therefore, the present invention is prepared according to the asphalt bending creep stiffness test (JTG E20-2011) specification, using Figure 6The mold shown in the figure is used to make the sample with a length of 127±5mm, a width of 12.7±0.25mm, and a height of 6.4±0.1mm. Figure 7 The bending rheometer shown in the figure tests the photocatalytic modified asphalt at -6°C, -12°C and -24°C for 240s. The S value and m value at 60s are used to evaluate the low-temperature crack resistance of the sample.

[0083] In order to explore the effect of the photocatalyst g-C3N4 / CeO2 / Bi2O3 / TOM prepared by the present invention on the low-temperature performance of asphalt, standard samples were prepared according to the photocatalyst dosage of 0wt%, 2wt%, 4wt%, 6wt%, and 8wt% of the asphalt mass, and the S and m values ​​of the photocatalytic modified asphalt at -6℃, -12℃, and -24℃ were tested by BBR test. The results are shown in Table 2. The S and m fitting relationships of the samples under each photocatalyst dosage are shown in Table 2. Figure 8 , as shown in 9.

[0084] Table 2 BBR test data of photocatalytic modified asphalt

[0085]

[0086]

[0087] from Figure 8 It can be seen that the low-temperature creep stiffness S of the photocatalytic modified asphalt shows an increasing trend with the increase of the photocatalyst content; and for the modified asphalt with the same photocatalyst content, as the temperature decreases, the low-temperature creep stiffness S value of the sample increases. In addition, it can be seen from the figure that the mass of the added photocatalyst has little effect on the creep stiffness of the modified asphalt, and the low amount of the photocatalyst may have little effect on the low-temperature performance of the modified asphalt; but compared with the matrix asphalt, the creep stiffness of the photocatalytic modified asphalt is significantly increased, indicating that the addition of the photocatalyst will have a negative effect on the low-temperature performance of the asphalt, indicating that the increase of the photocatalyst will increase the brittleness of the asphalt and weaken the asphalt's ability to resist deformation at low temperatures. However, when the temperature is higher than -12°C, the change in the low-temperature creep stiffness of the photocatalytic modified asphalt is not much different from that of the matrix asphalt, indicating that when the photocatalytic modified asphalt is used above this temperature, the addition of the photocatalyst can not only increase the asphalt's ability to purify exhaust gas but also does not affect the asphalt's low-temperature performance.

[0088] from Fig. 9It can be seen that the low-temperature creep rate m of the photocatalytic modified asphalt shows a trend of first decreasing and then increasing with the increase of the photocatalyst content; and for the modified asphalt with the same photocatalyst content, the lower the temperature, the smaller the creep rate m of the sample. When the photocatalyst content is less than 4wt%, the creep rate m of the modified asphalt gradually decreases with the increase of the photocatalyst content, indicating that the addition of the photocatalyst causes the accumulation rate of stress in the asphalt material to increase; and when the photocatalyst content is greater than 4wt%, the creep rate m of the modified asphalt gradually increases with the continued increase of the photocatalyst content, indicating that the increase in the photocatalyst content is conducive to improving the stress relaxation ability of the modified asphalt, thereby benefiting the low-temperature performance of the asphalt.

[0089] (5) Exhaust gas purification test of photocatalytic modified asphalt

[0090] According to the above preparation process, samples of photocatalytic modified asphalt with different dosages can be prepared. According to the above experimental steps, the samples are subjected to a photocatalytic exhaust gas degradation test. In order to verify whether the photocatalytic modified asphalt has the purification and degradation efficiency for exhaust gas, the present invention evenly spreads the sample asphalt on a glass plate or a wooden board with a size of 20mm*30mm and a thickness of about 1-2mm ( Fig.10 ), if the thickness is too thick, it may affect the light energy utilization rate of the photocatalyst.

[0091] The samples were placed in the exhaust gas purification system for testing, and the degradation efficiency of the four exhaust gas components under ultraviolet light and natural light conditions with different amounts of photocatalytic modified asphalt was obtained. Fig.11 shown.

[0092] Fig.11 The following are the degradation efficiency curves of the four components of tail gas under different dosage conditions of photocatalytic modified asphalt under ultraviolet light and natural light within 60 minutes. Fig.11It can be seen that the photocatalyst added to asphalt has the function of exhaust gas degradation, and with the increase of photocatalyst dosage, the exhaust gas degradation efficiency of modified asphalt gradually increases and the increment is more obvious, but when the photocatalyst content exceeds 4wt%, it can be seen that the degradation of tail gas by modified asphalt gradually tends to be stable and no longer increases. This may be due to the uneven distribution of photocatalysts with the increase of photocatalyst content and sinking to the bottom of asphalt to absorb less light, or it may be that excessive photocatalysts may produce agglomeration and reduce the utilization rate of light. The degradation efficiency of photocatalytic modified asphalt on HC, CO, CO2, and NOX with dosages of 0wt%, 2wt%, 4wt%, 6wt%, and 8wt% respectively under ultraviolet light and natural light conditions within 60 minutes was calculated, and the results are shown in Tables 3 and 4. For ease of description, the present invention records the matrix asphalt and the modified asphalt with photocatalyst dosages of 2wt%, 4wt%, 6wt%, and 8wt% as J1, J2, J3, J4, and J5 respectively.

[0093] Table 3 Degradation efficiency of modified asphalt on tail gas under ultraviolet light conditions

[0094]

[0095] Table 4 Degradation efficiency of modified asphalt on tail gas under natural light conditions

[0096]

[0097]

[0098] It can be seen intuitively from Table 3 and Table 4 that the photocatalytic modified asphalt formed by adding photocatalytic materials to asphalt still has a good degradation effect on automobile exhaust. Compared with the single photocatalytic material mentioned above, under ultraviolet light conditions, the degradation of HC, CO, CO2, NO X The degradation capacity within 60 minutes decreased by about 57%, 52%, 44% and 58% respectively; under natural light conditions, the degradation capacity of HC, CO, CO2 and NO X The degradation capacity decreased by about 58%, 52%, 35% and 52% respectively within 60 minutes. From the analysis results, the efficiency of photocatalytic degradation of tail gas by photocatalytic modified asphalt has been reduced, indicating that the utilization rate of light energy of photocatalytic materials in asphalt is very low, but the modified asphalt still has the ability to degrade tail gas, which also provides a new idea for environmental governance.

[0099] (6) Dispersion characteristics

[0100] In order to study the dispersion of photocatalyst in asphalt at different dosages, the dispersion performance of photocatalyst in asphalt was observed using an optical microscope produced by Shanghai Cewei Optoelectronic Technology Co., Ltd. Samples were prepared according to the preparation process. Fig.12 shown.

[0101] Fig.13 The dispersion characteristics of modified asphalt with different photocatalyst contents are observed using an optical microscope. From the test results, it can be seen that as the photocatalyst content gradually increases, the percentage of photocatalyst within the viewing angle gradually increases. When the photocatalyst content is less than 6wt% of the asphalt mass, the photocatalyst has good dispersibility in the asphalt, and therefore has good photocatalytic exhaust gas degradation efficiency; and when the photocatalyst content is greater than 6wt% of the asphalt mass, it can be clearly seen that the photocatalyst gradually agglomerates in the asphalt. This may be because the longer organic chains in the sample will entangle with each other, causing the photocatalytic material to agglomerate, or it may be because the amount of photocatalyst in the sample is too much and the dispersion is uneven, so that the purification efficiency of the photocatalytic modified asphalt for exhaust gas decreases instead of increases. Therefore, the photocatalyst content in the photocatalytic modified asphalt should be less than 6wt% of the asphalt mass.

[0102] The above examples are only the experimental and verification process of the present invention. Obviously, the verification of the present invention is not limited to the above examples. Any modifications and changes made to the present invention within the spirit of the present invention and the protection scope of the claims should be considered as the protection scope of the present invention.

Claims

1. A photocatalytic modified asphalt based on g-C3N4 / CeO2 / Bi2O3 / TOM, characterized in that: The modified asphalt comprises a base asphalt and a grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material accounting for 2 to 8 wt% of the base asphalt mass; wherein the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material is prepared by adding the g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material to a mixed solution of deionized water and anhydrous ethanol, ultrasonically treating the solution for 30 minutes, magnetically stirring the obtained mixed solution at 25°C for 15 minutes, adjusting the pH value to 12-14, adding a 40% methanol solution of DC5700, stirring the solution at 50°C at a speed of 1500 rpm for 3 hours, and then stirring the solution at a speed of 300 rpm for 1 hour, washing and filtering the solution multiple times to remove impurities, and drying the solution to obtain the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material.

2. The photocatalytic modified asphalt according to claim 1, characterized in that: The volume ratio of deionized water to anhydrous ethanol in the mixed solution of deionized water and anhydrous ethanol is 4:

1.

3. The photocatalytic modified asphalt according to claim 1, characterized in that: The mass ratio of g-C3N4 / CeO2 / Bi2O3 / TOM to DC5700 is 1:

2.

4. The photocatalytic modified asphalt according to claim 1, characterized in that: The g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material was prepared by the following steps: Step 1: Place g-C3N4, CeO2 and Bi(NO3)3·5H2O in a mixed solution of anhydrous ethanol and deionized water, stir evenly, add tourmaline powder, disperse by ultrasonic for 1 h, and then stir by magnetic stirring for 2 h; Step 2: After drying the suspension obtained in step 1, the obtained block solid is ground into powder; Step 3: Keep the above powder at 500°C for 4 hours, and then keep it at 450°C for 12 hours, and obtain g-C3N4 / CeO2 / Bi2O3 / TOM heterojunction photocatalytic material after cooling.

5. The photocatalytic modified asphalt according to claim 4, characterized in that: g-C3N4 is prepared by the following steps: dicyandiamide is heated at 600°C for 4 hours at a heating rate of 15°C / min; and g-C3N4 is obtained after cooling.

6. The photocatalytic modified asphalt according to claim 4, characterized in that: The mass of g-C3N4, CeO2 and Bi(NO3)3·5H2O is 3:4:14.55; the mass of tourmaline is 15% of the total mass of g-C3N4, CeO2 and Bi(NO3)3·5H2O.

7. The photocatalytic modified asphalt according to claim 4, characterized in that: The volume ratio of anhydrous ethanol to deionized water is 5:

3.

8. The photocatalytic modified asphalt according to claim 4, characterized in that: The sample was heated to 500°C at a heating rate of 15°C / min, and then kept at 450°C for 12 h.

9. A method for preparing g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic modified asphalt according to any one of claims 1 to 8, characterized in that: The steps include: The base asphalt is heated to 150±5°C, mixed with the grafted g-C3N4 / CeO2 / Bi2O3 / TOM photocatalytic material in a mixer at 300rpm and stirred for 30 minutes, and then sheared and stirred for 90 minutes at 2000rpm using a high-speed shearing machine to obtain the photocatalytic modified asphalt.